Analisis Hasil Kuat Tekan Beton Normal Terhadap Mix Design Kuat Tekan Beton Rencana - Paryati, Ninik; Nuryati, Sri; Yulius, Elma; Agussalim, Anita Mardiana (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Concrete Mix Design is the design of concrete using concrete constituent materials consisting of fine aggregate (sand), coarse aggregate (gravel), cement, water with added or not added ingredients, with the aim of obtaining the compressive strength of the planned concrete. One indicator of good concrete quality can be seen from the results of compressive strength testing, where the compressive strength of the resulting concrete must not be lower than the compressive strength of the planned concrete in the mix design. Mix design work must be carried out carefully and carefully because when determining the ratio and proportion of the concrete mixture you must pay attention to good concrete standards and meet the requirements, including compressive strength, workability (ease of work) and durability (concrete durability). The aim of this research is to find out what factors influence the compressive strength of normal concrete to be lower than the compressive strength of the planned concrete in the mix design, and to find out the difference between the compressive strength of the resulting normal concrete and the compressive strength of the planned concrete. The large number of concrete compressive strength results that do not match the strength of the mix design plan in many studies of Civil Engineering students at Islamic University 45 Bekasi is the basis for the need to carry out analysis so that the cause of the error can be identified, starting from filling in the mix design form, determining the ratio from the graph, the proportion of the mixture of the constituent materials. concrete, as well as the ratio of weight or volume of concrete used. The results of this research show that the compressive strength planned in the mix design was 20 Mpa, while the average compressive strength produced with a W/C of 0.59 was 17.5 Mpa, which decreased by 12.5%, while the average compressive strength produced with a W/C of 0.6 amounting to 22,667 Mpa, an increase of 13.3% from the design compressive strength, possibly because the water content is greater so it is easier to mold, so the concrete surface is flatter and the resulting compressive strength is greater. W/C is the ratio or comparison of the weight of water to the weight of cement and cementitious additives which are generally added to high quality concrete mixtures. The conclusion is that the factors that influence the compressive strength of normal concrete to be lower than the compressive strength of the planned concrete in the mix design are sand with a fine modulus of 3.0635, gravel with a fine modulus of 6.72. The average concrete compressive strength for W/C 0.59 is 17.5Mpa and the average concrete compressive strength for W/C 0.60 is 22,667 Mpa, so the difference between the two average compressive strengths is 5.2 Mpa, where with W/C 0.60 The resulting compressive strength of the concrete is better.